Transformasi Wakaf Tunai dalam Mewujudkan Kesejahteraan Sosial: Analisis Potensi dan Strategi Pendayagunaan Produktif - Bakhri, Saiful (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
Waqf serves as a pivotal social finance instrument within Islamic teachings, aimed at optimizing the economic potential and benefits of assets for both religious purposes and public welfare. As home to the world’s largest Muslim population—approximately 237.55 million people—Indonesia possesses immense potential for waqf fund accumulation. However, the development of waqf remains suboptimal and inadequately socialized due to several critical factors. These include a stagnant public understanding of waqf and the prevalence of traditional management practices among nazhirs (waqf managers). Consequently, waqf has yet to significantly impact poverty reduction or bridge the economic inequality gap in the country. If Indonesia successfully optimizes this vast waqf potential, particularly through cash waqf, social prosperity and national economic stability would be more effectively guaranteed.